Enhancing Behavioral Intention to Use Digital Wallets: The Role of Expectations and Social Influence - Pusporini, Pusporini; Handayani, Tati; Resti, Anggi Angga (Universitas Bumigora, 2024)
The use of digital wallets has become increasingly prevalent in various parts of the world, including Indonesia. People’s decisions to adopt digital wallet technology are influenced by several factors. This research aims to investigate the impact of performance expectations, effort expectations, and social influence on the behavioral intention to use digital wallets in Depok City. The method used is a descriptive associative method with a quantitative approach was employed in this study, and purposive sampling was used to select 120 respondents. The results of the study reveal that effort expectation and social influence have a significant positive effect on the behavioral intention to use digital wallets. Effort expectation refers to how easy and user-friendly the technology is perceived to be, while social influence pertains to the degree to which people are influenced by their social circles to adopt the technology. However, the study found that performance expectation, which relates to the perceived usefulness and advantages of digital wallets, did not have a significant impact on behavioral intention. This research contributes to the existing literature on technology adoption by highlighting the importance of user experience factors, such as effort expectation and social influence, in shaping consumers' behavioral intentions to use digital wallets. For practitioners, the findings suggest that efforts to increase the adoption of digital wallets should focus not only on enhancing the perceived usefulness of the technology but also on improving ease of use and leveraging social influence.